The Effect of Work Motivation, Organizational Commitment, and Leadership Style on Financial Management Accountability in Villages Moderated by Competency in Sikka Regency - Johanis W. Donbosko; Zulkifli Sultan; Juanda (Journal Research of Social Science, Economics, and Management, 2026)
Accountability in village financial management is a fundamental principle that must be implemented by village governments to ensure transparency and responsible use of public funds. However, various findings in Sikka Regency indicate weaknesses in financial administration, suggesting that internal organizational factors such as work motivation, organizational commitment, leadership style, and apparatus competency may influence the level of accountability. This study aims to analyze the effect of work motivation, organizational commitment, and leadership style on the accountability of village financial management, and to examine whether the competency of village apparatus moderates these relationships in Sikka Regency. The study employed a quantitative research approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from village government officials involved in the Village Financial Management Implementation Team (PPKD). The analysis was conducted using SmartPLS software to test the relationships between variables and the moderating effect of competency. The results show that work motivation, organizational commitment, and leadership style have a positive and significant effect on the accountability of village financial management. However, the competency of village apparatus does not moderate the relationship between these variables and financial management accountability. Organizational behavioral factors play an important role in improving accountability in village financial management. Strengthening motivation, commitment, and leadership quality among village officials is essential to promote transparent and responsible financial governance.